Early Christianity in the Lycus Valley - Huttner, U. (Ancient Judaism and Early Christianity, 2013)
In Early Christianity in the Lycus Valley , Ulrich Huttner explores the way Christians established communities and defined their position within their surroundings from the first to the fifth centuries. He shows that since the time of Paul the apostle, the cities Colossae, Hierapolis and Laodicea allowed Christians to expand and develop in their own way. Huttner uses a wide variety of sources, not only Christian texts - from Pauline letters to Byzantine hagiographies - but also inscriptions and archeological remains, to reconstruct the religious conflicts as well as cooperation between Christians, Jews and Pagans. The book reveals the importance of local conditions in the development of Early Christianity.